Teachers' Creativity in Teaching Islamic Education to Improve Students' Learning Discipline in Elementary Schools in Deli Derdang District - Harahap, Laila Rahmayani; Darlis, Ahmad (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to examine the role of creativity of Islamic Education (PAI) teachers at SDN101775 Sampali in improving student learning discipline. Using a qualitative approach with a phenomenological method, this study explores the experiences and meanings felt by teachers and students during the learning process. The research location at SDN101775 Sampali was chosen because of the relevance of the field conditions to the phenomenon being studied. The results indicate that the creativity of PAI teachers significantly influences the creation of a pleasant classroom atmosphere and motivates students to be disciplined in their learning. Various creative methods applied by teachers include active learning methods, the use of technology media, contextual learning, instilling values through stories, consistent application of class rules, rewards for students, and management of extracurricular activities that support discipline. Additionally, teachers serve as role models of discipline for students. With this approach, the learning process becomes more engaging and effective, leading to improved discipline and focus among students. The implications of this study emphasize that teacher creativity is a key factor in the success of learning and the development of students' disciplinary attitudes. This research highlights the importance of teacher innovation in PAI education as an effort to enhance the quality of basic education.